Young people’s attitudes towards the human rights of immigrants and refugees: An interview study - Markúsdóttir, Margrét A.; Aðalbjarnardóttir, Sigrún (Icelandic Journal of Education, 2015)
Research on young people’s civic awareness and engagement has been expanding from a primary focus on their political views (Kubow, Grossman, & Ninomiya, 2000) to an emphasis on their views on various societal issues, such as their attitudes towards different social and cultural groups, including immigrants (e.g. Torney-Purta, Lehmann, Oswald, & Schulz, 2001). Most of the research on young people’s attitudes towards immigrants has been conducted with questionnaires (e.g. Kerr, Sturman, Schulz, & Burge, 2010). This qualitative study, conducted in Iceland, is part of a larger research project on „Young people’s civic engagement in a democratic society“ which uses both quantitative and qualitative methods to collect and analyze data. The study presented here focuses on two issues: young people’s attitudes towards the rights of immigrants and their reception of refugees by using semi-structured in-depth interviews. Nineteen young people in two age groups, 15 and 19 years old, participated in the study. Thematic analysis was used to explore their views. The main results of the thematic analysis suggest two main themes for the issue of attitudes towards the rights of immigrants: “opportunities” and “we and the other” (othering). First, for the theme “opportunities”, three subthemes emerged. The first was the importance of language. These young people felt that learning Icelandic was key to immigrants participating in the society, but they also saw the difficulty that immigrants could face in learning it; thus inadequate competence in Icelandic could present obstacles, for example in getting a job. They also thought this could inhibit immigrants from getting to know people, making friends, and communicating in general. The second theme was equal rights: immigrants should be able to enjoy the same rights as other citizens, such as having a voice about social issues through the right to vote and to maintain their identity related to their cultural origins. The third theme was prejudice: the young people felt ...